2020
DOI: 10.3389/fnmol.2020.00125
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids, Endocannabinoids and Sleep

Abstract: Sleep is a vital function of the nervous system that contributes to brain and bodily homeostasis, energy levels, cognitive ability, and other key functions of a variety of organisms. Dysfunctional sleep induces neural problems and is a key part of almost all human psychiatric disorders including substance abuse disorders. The hypnotic effects of cannabis have long been known and there is increasing use of phytocannabinoids and other formulations as sleep aids. Thus, it is crucial to gain a better understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 195 publications
(261 reference statements)
4
82
0
2
Order By: Relevance
“…We systematically compared results between developing and adult mice and between males and females. We confirmed previous reports that enhancing the levels of 2-AG or AEA by inhibition of MAGL or FAAH respectively, enhanced sleep amount and bout length in adult males (Kesner and Lovinger, 2020;Pava et al, 2016), and we extend these findings by showing similar results in juvenile and adolescent males. In contrast, inhibition of MAGL or FAAH in developing and early adult females had minimal effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We systematically compared results between developing and adult mice and between males and females. We confirmed previous reports that enhancing the levels of 2-AG or AEA by inhibition of MAGL or FAAH respectively, enhanced sleep amount and bout length in adult males (Kesner and Lovinger, 2020;Pava et al, 2016), and we extend these findings by showing similar results in juvenile and adolescent males. In contrast, inhibition of MAGL or FAAH in developing and early adult females had minimal effects.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have used pharmacology or genetics to target the eCB system in rodents and have shown that enhancement of eCB signaling promotes NREM stability, whereas inhibition of eCB signaling causes NREM fragmentation (Bogathy et al, 2019;Huitron-Resendiz et al, 2004;Kesner and Lovinger, 2020;Pava et al, 2016;Santucci et al, 1996). Thus, eCB signaling is well positioned to support the highly coordinated neuronal activity that likely promotes the restorative actions of NREM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and rats, CBD doses ranging from ~2 to 40 mg/kg BW/day have been reported to induce sedative effects, improve sleep quality, and increase total sleep time ( 41 , 46 , 47 ). However, more recent work has reported CBD to have no influence on the sleep cycle in humans ( 48 ), and others argue that CBD by itself does not produce sedative effects but rather modulates the sedative effect of Δ 9 -tetrahydrocannabinol (THC), even if THC is only present in minute amounts ( 42 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dissociated culture engage in a default sleep-like state where the network fires in synchronized bursts reminiscent of cortical up-states (Canepari et al, 1997;Kamioka et al, 1996b;Maeda et al, 1995;Robinson et al, 1993;Saberi-Moghadam et al, 2018). Tonic CB1 signaling has been shown to support up-state activity in organotypic slices in vitro, and NREM sleep stability in vivo (Kesner and Lovinger, 2020;Pava et al, 2014). We show here that tonic CB1 signaling is similarly required to support NREM like up-states in dissociated cortical cultures.…”
Section: Cb1 Cortical Up-states and Nrem Sleepmentioning
confidence: 99%